Implementasi RME Melalui Pengembangan Model Intelligence Quotient Guna Meningkatkan Mutu Rumah Sakit - Faida, Eka Wilda; Saadah, Alfina Aisatus; Sutha, Diah Wijayanti; Ali, Amir; Haryono, Hendri (J-REMI : Jurnal Rekam Medik dan Informasi Kesehatan, 2025)
The main challenges in developing a national health data system in Indonesia include the fact that more than 80% of healthcare facilities remain undigitalized, data fragmentation, and limited regulations on data standardization and interoperability, which are not yet aligned with the Ministry of Health’s 2024 mandate. Fulfilling this mandate requires continuous and real-time access to medical records, as well as data completeness, consistency, accuracy, and the prevention of work duplication among Electronic Medical Record (EMR) users. Intelligence Quotient (IQ), encompassing intellectual, emotional, and spiritual intelligence, significantly influences employee performance and hospital quality. This study aims to develop an IQ model using the End User Computing Satisfaction (EUCS) approach to measure job satisfaction and performance in hospitals. Data were collected through a cross-sectional questionnaire and analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) and Importance Performance Matrix Analysis (IPMA). The results show that IQ has a direct effect on net benefits and an indirect effect through EUCS and satisfaction, with an R-square value of 71% for satisfaction, indicating a strong influence. Efforts to enhance IQ should focus on improving problem-solving abilities, self-awareness, self- and relationship management, flexibility, resilience, and adherence to regulations.